Evaluation of Bedtime Oral Hygiene Behavior and Dietary Habits in Children - S. Ceren İlisulu; Edmon Sakız; Mustafa Küçük (European Annals of Dental Sciences)

(untitled)
Purpose: The purpose of this study was to assess the effect of bedtime oral hygiene and dietary behaviors on dental health in children.Materials & Methods: For this study, 83 parents with children aged 6 to 8 years participated. All participants who agreed to take part in the study were called on their mobile phones during 7 days (weekdays and weekend) for collecting data of bedtime routine activities of children including oral hygiene behaviors and dietary habits 1 hour before bedtime. Children’s clinical oral examination were carried out by trained and calibrated pediatric dentist following WHO guideline 2013. IBM SPSS Statistics (version 22.0) was used for all statistical analyses, including the Mann Whitney U test, the Kruskal Wallis test, and the Kolmogorov-Smirnov test.Results: The dmft score of children who were allowed to eat or drink 1 hour before bedtime was statistically significantly higher than those who were not allowed (p=0.014; p0.05)Conclusion: The present study highlighted bedtime dietary habits affect the dental health of children. Establishing optimal bedtime routines, including oral hygiene practices and dietary habits, is essential for proper oral hygiene and the well-being and development of children.